2015
DOI: 10.1190/int-2015-0067.1
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of soils in a designated Natura area (GR4310010, Giouchtas Mountain)

Abstract: The magnetic behavior of the geologic formations around the Giouchtas or Juchtas Mountain (Mt.) in Central Crete, Greece, has been studied. The magnetic parameters (magnetic susceptibility [MS] and temperature dependence of the magnetic susceptibility) of 160 surface soil samples were interpreted based on available information (e.g., topographic, geologic, and historical) for the area of study. The soil samples have been collected from the low-and high-elevation regions of Giouchtas Mt. The low-elevation regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…Kokinou et al ( 2013 ) conducted a geophysical survey in the study area using magnetic susceptibility and thermomagnetism (Hansen et al, 1981 ; Petrovsky & Ellwood, 1999 ; Thompson & Oldfield, 1986 ) to identify sites with contaminated topsoil (Bityukova et al, 1999 ; Boyko et al, 2004 ; Petrovsky et al, 2001 ; Scholger, 1998 ) regarding heavy metals (Goluchowska, 2001 ; Kokinou, 2015 ; Sarris et al, 2009 ; Strzyszcz et al, 1996 ). The geophysical data were interpreted considering the area’s topography, geology, urban network and blowing winds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kokinou et al ( 2013 ) conducted a geophysical survey in the study area using magnetic susceptibility and thermomagnetism (Hansen et al, 1981 ; Petrovsky & Ellwood, 1999 ; Thompson & Oldfield, 1986 ) to identify sites with contaminated topsoil (Bityukova et al, 1999 ; Boyko et al, 2004 ; Petrovsky et al, 2001 ; Scholger, 1998 ) regarding heavy metals (Goluchowska, 2001 ; Kokinou, 2015 ; Sarris et al, 2009 ; Strzyszcz et al, 1996 ). The geophysical data were interpreted considering the area’s topography, geology, urban network and blowing winds.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the frequencydependent susceptibility (χ FD %) was calculated using the formula: χ FD (%) = [(χ LF -χ HF )/χ LF ]x100, where χ LF is the susceptibility measured at low frequency, and χ HF is the susceptibility measured at high frequency. Kokinou et al (2013) conducted a geophysical survey in the study area using magnetic susceptibility and thermomagnetism (Hansen et al, 1981;Petrovsky & Ellwood, 1999;Thompson & Oldfield, 1986) to identify sites with contaminated topsoil (Bityukova et al, 1999;Boyko et al, 2004;Petrovsky et al, 2001;Scholger, 1998) regarding heavy metals (Goluchowska, 2001;Kokinou, 2015;Sarris et al, 2009;Strzyszcz et al, 1996). The geophysical data were interpreted considering the area's topography, geology, urban network and blowing winds.…”
Section: Geophysical Analysesmentioning
confidence: 99%
“…Karteros Gorge is part of a larger geological complex of the Giouchtas Ecological Park in Archanes (https://landofexperiences.gr/travels/karterosgorge/ (accessed on 15 October 2023)). The park includes Giouchtas Mountain [33][34][35] and three gorges: Knosanos, Kounaviano, and Astrakanos or Karteros gorge, with a total length of 22 km. The entire area is environmentally protected (Natura 2000 network).…”
Section: The Environment Of This Studymentioning
confidence: 99%
“…Topsoil samples were collected along the Karteros Stream, and GPS coordinates (in EGSA_87 system) were taken from each sampling location to match the available topographic data. Topsoil samples from area I were analysed for magnetic susceptibility using well-tested methodology, already applied in previous studies [23][24][25]34,41], to investigate the study area for possible heavy-metal concentrations [25,34,[42][43][44][45]. In environmental magnetism [46], the most used magnetic parameter is magnetic susceptibility (χ), which is the ratio of the induced magnetisation of a sample in the presence of a weak magnetic field to the applied field itself.…”
Section: Geophysical Analyses Of Soil and Watermentioning
confidence: 99%
“…So, on our example of Kupa River, it was the confirmed finding of [27] that concluded that two powerful applications of susceptibility measurements of soils (and sediments in our case) exist: the identification of polluted areas and the detailed mapping of these areas to reveal the extent of pollution. The other study [28] conducted in a designated Natura area of Giouchtas Mountain, Crete, Greece showed that studying the magnetic properties of surface soils, along with existing information, allowed the authors to characterize the natural and anthropogenic impacts.…”
Section: Magnetic Susceptibility Of Sedimentsmentioning
confidence: 99%